Clustering‐Induced White Light Emission from Carbonized Polymer Dots. Issue 5 (5th May 2021) - Liu, Bin; Chen, Zheng; Chu, Bo; Wang, Ya-Ling; Li, Ning; Zhang, Huinian; Yang, Yongzhen; Hu, Shengliang; Zhang, Xing-Hong
Abstract : White Light‐Emitting Carbon Dots In article number 2000161, Bin Liu, Xing‐Hong Zhang, and co‐workers prepare a white‐light‐emitting carbonized polymer dot by a solvothermal method. A multi‐cluster‐induced luminescence mechanism is proposed to account for the observed luminescence. Loose clusters formed from hydroxyurethane and C=N bonds emit blue light, whereas compact clusters generated through interactions between the hydroxyurethane and C=N bonds of poly(hydroxyurethane) and carbon cores emit yellow light, thereby leading to white light emission.